O efeito do desempenho de um papel de ajuda na ansiedade de falar em público: um estudo experimental - Franco, Angela Maria Monteiro da Silva (1982)
This research had for' its principal aim to verify the 'helper principle', a phenomenon that emphasizes the benefits we receive whenever we help someone else. In order to fulfill this aim, subjects with high speech anxiety played the helper's role: they played the 'behavioral therapists' to other subjects with speech anxiety. After being selected, the subjects with high speech anxiety were distributed into the following experimental groups: 1) group whose subjects learned from therapists about behavioral techniques to reduce speech anxiety, and, subsequently, taught these techniques to other subjects; 2) group in which the subjects learned from therapists about the techniques to reduce speech anxiety, but did not teach them to other subjects; 3) group which learned the techniques from subjects from group one; 4) group whose subjects only participated in pre and post-test periods. A better performance of group one, if compared to group two, towards a considerable larger reduction of speech anxiety, had been foreseen, for the former would play a helping role. However, the statistical inferences pointed out that the substantive hypothesis was rejected: group one did not have its anxiety significantly more reduced than group two, although the groups which received the speech-anxiety-reduction -training progam (groups 1, 2 and 3) had significantly improved more than group four. Possible explanations for these resu1ts are 1ikely to be discussed and also suggestions for new researches might as well be made.